Identification of Novel Coxiella burnetii Genotypes from Ethiopian Ticks - Sulyok, Kinga M.; Hornok, Sándor; Abichu, Getachew; Erdélyi, Károly; Gyuranecz, Miklós (PloS one, 2014)
Coxiella burnetii, the etiologic agent of Q fever, is a highly infectious zoonotic bacterium. Genetic information about the strains of this worldwide distributed agent circulating on the African continent is limited. The aim of the present study was the genetic characterization of C. burnetii DNA samples detected in ticks collected from Ethiopian cattle and their comparison with other genotypes found previously in other parts of the world. A total of 296 tick samples were screened by real-time PCR targeting the IS1111 region of C. burnetii genome and from the 32 positive samples, 8 cases with sufficient C. burnetii DNA load (Amblyomma cohaerens, n = 6; A. variegatum, n = 2) were characterized by multispacer sequence typing (MST) and multiple-locus variable-number tandem repeat analysis (MLVA). One novel sequence type (ST), the proposed ST52, was identified by MST. The MLVA-6 discriminated the proposed ST52 into two newly identified MLVA genotypes: type 24 or AH was detected in both Amblyomma species while type 26 or AI was found only in A. cohaerens. Both the MST and MLVA genotypes of the present work are closely related to previously described genotypes found primarily in cattle samples from different parts of the globe. This finding is congruent with the source hosts of the analyzed Ethiopian ticks, as these were also collected from cattle. The present study provides genotype information of C. burnetii from this seldom studied East-African region as well as further evidence for the presumed host-specific adaptation of this agent.